The problem of systemic violation of civil and political rights in Cameroon : towards a contextualised conception of constitutionalism - Enonchong, Laura-Stella (2013)
Post-independent Cameroon has grappled with the problem of systemic violation of civil and political rights (CPR) despite a transition from single party dictatorship to multiparty democracy in the 1990s. Various legislative measures including the adoption of a supposedly ‘rights friendly’ constitution in 1996 have done little to ameliorate that problem. This thesis adopts a concept of constitutionalism, based on contemporary international standards, to analyse the problem of CPR violations from the perspective of the constitutional arrangements in Cameroon. It examines the system of separation of powers, the method of securing judicial independence and the mechanisms for judicial review. The argument is made that the problem can be attributed in part to the predominant influence of the French civil law system in Cameroon’s bijural legal system. Although for historical reasons, Cameroon operates both the English common law and the French civil law, constitutional developments have continued to be influenced by the latter which lends itself to practices that are not sufficiently supportive of constitutionalism as defined herein. The thesis, however, goes further to explore how the constitutional system could be reinforced to provide a more conducive framework for the protection and enhancement of CPR. Drawing on two strands of arguments, one highlighting features of the common law system that can be more supportive of constitutionalism and the other which highlights the value of indigenous antecedents of constitutionalism, the thesis proposes the development of a contextual model which is more reflective of Cameroon’s peculiar legal and socio-political circumstances. It proposes what is described as an Optimal Integrative Approach (OIA) as a framework for developing a contextual model, more conducive for the protection and enhancement of CPR in Cameroon.